Assessment of Healthcare System Capabilities and Preparedness in Yemen to Confront the Novel Coronavirus 2019 (COVID-19) Outbreak: A Perspective of Healthcare Workers - Zawiah, Mohammed; Al-Ashwal, Fahmi Y.; Saeed, Ramzi Mukred; Kubas, Mohammed; Saeed, Sara; Khan, Amer Hayat; Sulaiman, Syed Azhar Syed; Abduljabbar, Rami (Frontiers in Public Health, 2020)
Background: In the past decade, Yemen has witnessed several disasters that resulted in a crumbled healthcare system. With the declaration of COVID-19 a global pandemic, and later the appearance of first confirmed cases in Yemen, there is an urgent need to assess the preparedness of healthcare facilities (HCFs) and their capacities to tackle a looming COVID-19 outbreak. Herein, we present an assessment of the current state of preparedness and capabilities of HCFs in Yemen to prevent and manage the COVID-19 outbreak. Methods: An online survey for HCFs was developed, validated, and distributed. The questionnaire is divided into five main sections: (1) Demographic variables for participants. (2) HCFs capabilities for COVID-19 outbreak. (3) Support received to face the emergence and spread of COVID-19. (4). Current practices of infection prevention and control measures in the HCFs. The last section focused on the recommendations to ensure effective and timely response to this outbreak in Yemen. Descriptive analysis was used to analyze data using statistical package for social sciences (SPSS), version 23. Results: Responses were received from healthcare workers (HCWs) from 18 out of 22 governorates in Yemen. Out of the 296 HCWs who participated in the study, the vast majority (93.9%) believed that the healthcare system in Yemen does not have the resources and capabilities to face and manage a COVID-19 outbreak. Approximately 82.4% of participants rated the general preparedness level of their HCFs as very poor or poor. More specifically, the majority of HCWs rated their HCFs as very poor or poor in term of availability of the following: an adequate number of mechanical ventilators (88.8%), diagnostic devices (88.2%), ICU rooms and beds (81.4%), and isolation rooms (79.7%). Conclusions: The healthcare facilities in Yemen are unprepared and lack the most basic resources and capabilities to cope with or tackle a COVID-19 outbreak. With the current state of a fragile healthcare system, a widespread outbreak of COVID-19 in Yemen could result in devastating consequences. There is an urgent need to provide support to the healthcare workers and HCFs that are on the frontline against COVID-19.